3 Bernard Bush, Laws of the Royal Colony of New Jersey 307 (1980) - (:unkn) unknown (My University, 1755)
Set the minimum age at twenty-one for enlistment for out-of-colony service without consent of a parent, guardian, or master.
Keywords: ARMED FORCES